2017
DOI: 10.3892/mco.2017.1422
|View full text |Cite
|
Sign up to set email alerts
|

Successful and long-term response to trastuzumab plus paclitaxel combination therapy in human epidermal growth factor receptor 2-positive extramammary Paget's disease: A case report and review of the literature

Abstract: A 58-year-old woman with a histologically confirmed diagnosis of vulvar extramammary Paget's disease (EMPD) was referred to our hospital due to locally advanced and relapsed EMPD. The patient had undergone surgical resection three times for relapsed vulvar EMPD over a period of 12 years, but developed locally advanced and unresectable EMPD. As pathological examination indicated that the lesion was positive for human epidermal growth factor receptor 2 (HER2) on immunohistochemical staining, the patient was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 13 publications
(20 reference statements)
0
37
1
Order By: Relevance
“…Furthermore, about 90% of patients exhibited no difference in the HER2 protein overexpression and ERBB2 gene amplification between primary tumors and corresponded LN metastasis ( 23 ), suggesting that HER2’s contribution to the pathogenesis and progression in a subset of metastatic EMPD and implying the possibility that HER2 blockade disrupts the progression of both primary and metastatic lesions of this population. In corroboration with the hypothesis, six case reports determined that both primary and metastatic lesion of HER2-overexpressed EMPD responded well and attained partial or complete response for 6 months to 2 years by anti-HER2 antibody, trastuzumab alone, or trastuzumab with paclitaxel (Table 1 ) ( 24 29 ). A phase 2 study of trastuzumab with docetaxel for HER2-positive unresectable or metastatic EMPD (UMIN000021311) is ongoing based on these results.…”
Section: Her2–pi3k/erk Signaling In Empdmentioning
confidence: 64%
“…Furthermore, about 90% of patients exhibited no difference in the HER2 protein overexpression and ERBB2 gene amplification between primary tumors and corresponded LN metastasis ( 23 ), suggesting that HER2’s contribution to the pathogenesis and progression in a subset of metastatic EMPD and implying the possibility that HER2 blockade disrupts the progression of both primary and metastatic lesions of this population. In corroboration with the hypothesis, six case reports determined that both primary and metastatic lesion of HER2-overexpressed EMPD responded well and attained partial or complete response for 6 months to 2 years by anti-HER2 antibody, trastuzumab alone, or trastuzumab with paclitaxel (Table 1 ) ( 24 29 ). A phase 2 study of trastuzumab with docetaxel for HER2-positive unresectable or metastatic EMPD (UMIN000021311) is ongoing based on these results.…”
Section: Her2–pi3k/erk Signaling In Empdmentioning
confidence: 64%
“…Selected cases of EMPD (with amplified ERBB2/HER2 gene) have been successfully treated with trastuzumab alone or in combinations with chemotherapy. 4,[15][16][17][18][19][20][21] In contrast to MPD, we found overexpression and HER2 gene amplification in a minority of cases, and a co-amplification with TOPO2 in a single case of vulvar disease. Amplification of TOPO2 gene and expression of Topo2 protein in several cases of EMPD is a novel finding in our cohort.…”
Section: Discussionmentioning
confidence: 97%
“…5 Except for traditional chemotherapy, previous studies have reported HER2-targeted monoclonal antibody (trastuzumab) could yield significant clinical benefit in lymph node-metastatic penoscrotal EMPD patients with HER2 amplification. 9 Pyrotinib is an oral irreversible tyrosine kinase inhibitor capable of inhibiting the HER1, HER2, and HER4. Until now, there has been no any report about the effectiveness of pyrotinib in those patients with HER2 gene alteration.…”
mentioning
confidence: 99%